Battery

JP7634187B2Active Publication Date: 2025-02-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022501658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-20
Filing Date
2020-12-22
Publication Date
2025-02-21
Estimated Expiration
2040-12-22

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、電池の発熱を抑制することができる、信頼性が高い電池を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634187000001
    Figure 0007634187000001
  • Figure 0007634187000002
    Figure 0007634187000002
  • Figure 0007634187000003
    Figure 0007634187000003
Patent Text Reader

Abstract

This battery comprises: a first solid-state battery cell; and a buffer layer. The first solid-state battery cell comprises: a positive electrode; a negative electrode; and a solid electrolyte layer positioned between the positive electrode and the negative electrode. The positive electrode or the negative electrode includes a collector. The buffer layer is in contact with a surface of the collector on the side opposite the solid-state electrolyte layer. The buffer layer contains a PTC material, a resin, and a first metal, the first metal being at least one selected from the group consisting of Sn, Cu, Al, Mg and Zn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to batteries. [Background technology]

[0002] Batteries may suddenly generate heat due to a short circuit or the like. As a technology for suppressing such an increase in battery temperature, for example, Patent Document 1 discloses an all-solid-state battery in which a current collector with PTC (Positive Temperature Coefficient) characteristics is formed on a positive electrode active material. Patent Document 2 discloses an all-solid-state battery in which a PTC layer is disposed between an active material layer and a current collector. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-130281 A [Patent Document 2] JP 2018-116810 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the prior art, there is a need to suppress heat generation in the battery.

[0005] Therefore, the present disclosure provides a highly reliable battery capable of suppressing heat generation in the battery. [Means for solving the problem]

[0006] A battery according to one embodiment of the present disclosure includes a first solid-state battery cell and a buffer layer. The first solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode. The positive electrode or the negative electrode has a current collector. The buffer layer is in contact with a surface of the current collector opposite to the solid electrolyte layer. The buffer layer includes a PTC material, a resin, and a first metal. The first metal is at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn. Effect of the Invention

[0007] According to the present disclosure, it is possible to realize a highly reliable battery that can suppress heat generation in the battery. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a battery according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing a schematic configuration of a battery according to a first modification of the embodiment. [Diagram 3] FIG. 3 is a diagram showing a schematic configuration of a battery according to a second modification of the embodiment. [Figure 4] FIG. 4 is a diagram showing a schematic configuration of a battery according to a third modification of the embodiment. [Diagram 5] FIG. 5 is a diagram showing a schematic configuration of a particulate PTC material and a first metal layer in a buffer layer of a battery according to a fourth modification of the embodiment. [Figure 6] FIG. 6 is a diagram showing a schematic configuration of a stacked battery according to a fifth modification of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Summary of the Disclosure) A battery according to an embodiment of the present disclosure includes a first solid-state battery cell and a buffer layer. The first solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode. The positive electrode or the negative electrode has a current collector. The buffer layer contacts a surface of the current collector opposite to the solid electrolyte layer. The buffer layer includes a PTC material, a resin, and a first metal. The first metal is at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn.

[0010] For example, when a barium titanate (BaTiO3)-based semiconductor PTC material, which is easily reduced, is used in a battery, there is a problem of reduction degradation. Specifically, when the PTC material is reduced, the switching characteristic to a high resistance state that cuts off the current is lost. In addition, there is a problem that the battery characteristics deteriorate due to high resistance loss caused by non-ohmic contact between the PTC material and the current collector.

[0011] In contrast, in the battery according to the above embodiment, the buffer layer contains a PTC material, a resin, and a first metal, which can solve the above problems. Specifically, the buffer layer contains a resin, which makes it possible to realize a buffer layer that is softer than the battery components, and therefore the buffer layer and the current collector can be joined with high reliability.

[0012] Furthermore, Sn, Cu, Al, Mg, or Zn has a lower work function than the surface of the PTC material, which is a BaTiO3-based semiconductor, so that the first metal can ensure low-resistance ohmic contact with the PTC material.

[0013] In addition, by having the PTC material and the first metal in ohmic contact with the PTC material coexist in the resin, the resistance loss can be reduced. Furthermore, the PTC material can be protected from reducing atmospheres while absorbing the stress of impacts and thermal cycles. In this way, the battery can be provided with PTC characteristics that are highly environmentally resistant and have low loss.

[0014] Therefore, when the battery generates abnormal heat, the buffer layer reliably becomes highly resistant, and the effect of cutting off the current is obtained. In other words, the buffer layer having the PTC characteristic functions as a current cutoff mechanism when heat is generated. In addition, in the normal battery operating state in which the PTC characteristic does not operate, since there is no polarity due to ohmic contact, the loss of battery characteristics during both charging and discharging is suppressed to a small extent. Therefore, a highly reliable and high-performance battery that can suppress fire or smoke-generating combustion can be provided.

[0015] Furthermore, for example, the first metal may be at least one selected from the group consisting of Sn, Al, Mg, and Zn.

[0016] This improves the electronic conductivity of the buffer layer, resulting in a battery with PTC characteristics and even smaller resistance loss.

[0017] For example, the buffer layer may include a PTC layer and a conductive resin layer. The PTC layer may include the PTC material, and the conductive resin layer may include the resin and the first metal, but may not include the PTC material. The conductive resin layer may cover a surface of the PTC layer opposite to the current collector.

[0018] This allows the conductive resin layer to protect one side of the PTC layer while also ensuring ohmic contact with the PTC layer, resulting in a battery with PTC characteristics that is highly reliable and resistant to external stress while suppressing resistance loss that affects battery characteristics.

[0019] Furthermore, for example, the conductive resin layer may further cover the surface of the PTC layer facing the current collector.

[0020] This allows the conductive resin layer to protect the PTC layer from both sides while also ensuring ohmic contact with the PTC layer and the current collector, making it possible to obtain a battery with PTC characteristics that is highly reliable and resistant to external stress while suppressing resistance loss that affects battery characteristics.

[0021] For example, the buffer layer may include a metal layer covering the surface of the PTC layer facing the current collector, and the metal layer may contain the first metal.

[0022] This ensures that the metal layer is in ohmic contact with the PTC layer and the current collector, thereby suppressing resistance loss that affects the battery characteristics.

[0023] For example, the buffer layer may include an alloy layer in contact with the current collector, the alloy layer being made of an alloy containing a second metal, and the second metal may be at least one selected from the group consisting of Sn, Ag, Cu, Bi, Al, and Zn.

[0024] This allows the buffer layer to secure a strong connection to the current collector via the alloy layer while ensuring low-resistance ohmic contact with the current collector.

[0025] Furthermore, for example, the second metal may be at least one selected from the group consisting of Sn, Bi, Al, and Zn.

[0026] This allows the buffer layer to secure a strong connection to the current collector via the alloy layer while ensuring low-resistance ohmic contact with the current collector.

[0027] Also, for example, the PTC material may be particles, and the particles may be coated with the first metal.

[0028] This allows the characteristics of all the PTC particles in ohmic contact to be brought out. This further reduces the loss of battery characteristics. In addition, the PTC material, which is vulnerable to environmental resistance, can be further protected, realizing highly reliable PTC characteristics. This allows the provision of a high-performance battery that can suppress ignition or combustion with smoke.

[0029] For example, the battery according to an embodiment of the present disclosure may further include a second solid-state battery cell. The first solid-state battery cell and the second solid-state battery cell may be stacked with the buffer layer interposed therebetween.

[0030] This makes it possible to realize a highly reliable, high-performance stacked battery that can suppress fire or smoking combustion without deteriorating the characteristics of the battery even in a multi-layered battery.

[0031] For example, the solid electrolyte layer may include a solid electrolyte having lithium ion conductivity.

[0032] Hereinafter, the embodiment will be described in detail with reference to the drawings.

[0033] The embodiments described below are all comprehensive or specific examples. The numerical values, shapes, materials, components, arrangement positions and connection forms of the components shown in the following embodiments are merely examples and are not intended to limit the present disclosure. Furthermore, among the components in the following embodiments, components that are not described in the independent claims are described as optional components.

[0034] In addition, the drawings are not necessarily strict illustrations. In the drawings, the same reference numerals are used for substantially the same configurations, and duplicated explanations are omitted or simplified.

[0035] In this specification and the drawings, the x-axis, y-axis, and z-axis represent the three axes of a three-dimensional Cartesian coordinate system. In each embodiment, the z-axis direction is the thickness direction of the battery. In this specification, the "thickness direction" refers to the direction perpendicular to the surface on which each layer is stacked.

[0036] In addition, in this specification, "plan view" refers to the case where the battery is viewed along the stacking direction of the battery, and "thickness" in this specification refers to the length of the battery and each layer in the stacking direction.

[0037] In addition, in this specification, the terms "inside" and "outside" refer to the inside and outside when the battery is viewed along the stacking direction of the battery.

[0038] In this specification, the terms "upper" and "lower" in the battery configuration do not refer to the upper direction (vertically upward) and lower direction (vertically downward) in absolute spatial recognition, but are used as terms defined by a relative positional relationship based on the stacking order in the stacking configuration. In addition, the terms "upper" and "lower" are applied not only to the case where two components are arranged with a gap between them and another component is present between the two components, but also to the case where two components are arranged in close contact with each other and the two components are in contact with each other.

[0039] (Embodiment) [Battery Overview] First, the battery according to the present embodiment will be described.

[0040] Fig. 1 is a diagram showing a schematic configuration of a battery according to the present embodiment. Specifically, Fig. 1(a) is a cross-sectional view of a battery 1 according to the present embodiment, and Fig. 1(b) is a plan view of the battery 1 as viewed from the positive side in the z-axis direction. Fig. 1(a) shows a cross section taken at the position indicated by line II in Fig. 1(b). Fig. 1(c) is a cross-sectional view in which a part of the cross-sectional shape shown in Fig. 1(a) is enlarged in schematic form.

[0041] 1, the battery 1 includes a solid-state battery cell 2 and a buffer layer 40. The battery 1 is an all-solid-state battery.

[0042] The solid battery cell 2 is an example of a first solid battery cell, and includes a first electrode 10, a second electrode 20, and a solid electrolyte layer 30. The first electrode 10 has a first current collector 11 and a first active material layer 12 arranged in contact with the first current collector 11. The second electrode 20 is a counter electrode of the first electrode 10, and has a second current collector 21 and a second active material layer 22 arranged in contact with the second current collector 21. The solid electrolyte layer 30 is located between the first electrode 10 and the second electrode 20, and is in contact with the first active material layer 12 and the second active material layer 22. The buffer layer 40 is in contact with the surface of the first current collector 11 opposite to the solid electrolyte layer 30. The buffer layer 40 includes a PTC material 41, a first metal 42, and a resin 43.

[0043] 1, the first current collector 11 and the buffer layer 40 of the solid-state battery cell 2 have the same shape, position, and size in a plan view. It is advantageous from the viewpoint of reducing resistance at the contact portion that the entire surface of the first current collector 11 facing the buffer layer 40 is in contact with the buffer layer 40.

[0044] [Solid-state battery cells] Each component of the solid-state battery cell 2 will be described in detail below.

[0045] The first current collector 11, the first active material layer 12, the solid electrolyte layer 30, the second active material layer 22, the second current collector 21, and the buffer layer 40 are each rectangular in a planar view. The shapes of the first current collector 11, the first active material layer 12, the solid electrolyte layer 30, the second active material layer 22, the second current collector 21, and the buffer layer 40 in a planar view are not particularly limited, and may be shapes other than a rectangle, such as a circle, an ellipse, or a polygon.

[0046] In this embodiment, the first electrode 10 is a positive electrode, and the second electrode 20 is a negative electrode. That is, the first current collector 11 is a positive electrode current collector, and the first active material layer 12 is a positive electrode active material layer. The second current collector 21 is a negative electrode current collector, and the second active material layer 22 is a negative electrode active material layer. The buffer layer 40 is connected to the positive electrode current collector.

[0047] The first electrode 10 may be a negative electrode, and the second electrode 20 may be a positive electrode. That is, the first current collector 11 may be a negative electrode current collector, and the first active material layer 12 may be a negative electrode active material layer. The second current collector 21 may be a positive electrode current collector, and the second active material layer 22 may be a positive electrode active material layer. The buffer layer 40 may be connected to the negative electrode current collector.

[0048] In this specification, the first current collector 11 and the second current collector 21 may be collectively referred to simply as "current collectors." The current collectors are not particularly limited as long as they are made of a material having electrical conductivity.

[0049] The current collector may be, for example, a foil, plate, or mesh made of stainless steel, nickel (Ni), aluminum (Al), iron (Fe), titanium (Ti), copper (Cu), palladium (Pd), gold (Au), or platinum (Pt), or an alloy of two or more of these. The material of the current collector may be appropriately selected in consideration of the fact that it does not melt or decompose in the manufacturing process, the temperature and pressure of use, and the operating potential and conductivity of the battery applied to the current collector. The material of the current collector may also be selected according to the required tensile strength and heat resistance. The current collector may be, for example, a high-strength electrolytic copper foil, or a clad material in which different metal foils are laminated.

[0050] The thickness of the current collector is, for example, in the range of 10 μm or more and 100 μm or less. The surface of the current collector may be processed to have an uneven rough surface in order to strengthen the adhesion with the first active material layer 12, the second active material layer 22, and the buffer layer 40. The surface of the current collector may be coated with an adhesive component such as an organic binder. This strengthens the adhesion at the interface between the current collector and other layers, and improves the reliability of the PTC characteristics not only in terms of the mechanical and thermal reliability of the battery and the cycle characteristics, but also in terms of the adhesion with the buffer layer 40.

[0051] The first active material layer 12 is disposed in contact with one surface of the first current collector 11. In the present embodiment, since the first active material layer 12 is a positive electrode active material layer, the first active material layer 12 contains at least a positive electrode active material. The first active material layer 12 is mainly a layer composed of a positive electrode material such as a positive electrode active material. The positive electrode active material is a material in which metal ions such as lithium (Li) ions or magnesium (Mg) ions are inserted or removed into or from the crystal structure at a potential higher than that of the negative electrode, and oxidation or reduction is performed accordingly. The type of the positive electrode active material can be appropriately selected according to the type of the battery, and known positive electrode active materials can be used.

[0052] Examples of the positive electrode active material include compounds containing lithium and a transition metal element, such as oxides containing lithium and a transition metal element, and phosphate compounds containing lithium and a transition metal element. Examples of the oxide containing lithium and a transition metal element include x M 1-x lithium nickel composite oxides such as O2 (where M is at least one element of Co, Al, Mn, V, Cr, Mg, Ca, Ti, Zr, Nb, Mo, and W, and x is 0 < x ≦ 1), layered oxides such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and lithium manganate (LiMn2O4), or lithium manganate having a spinel structure (for example, LiMn2O4, Li2MnO3, LiMnO2), etc. are used. Examples of the phosphate compound containing lithium and a transition metal element include lithium iron phosphate (LiFePO4) having an olivine structure. In addition, sulfides such as sulfur (S) and lithium sulfide (Li2S) can also be used as the positive electrode active material. In that case, a material obtained by coating or adding lithium niobate (LiNbO3) or the like to the positive electrode active material particles can be used as the positive electrode active material. Note that only one type of these materials may be used as the positive electrode active material, or two or more types of these materials may be combined and used.

[0053] As described above, the first active material layer 12 that becomes the positive electrode active material layer may contain at least a positive electrode active material. The positive electrode active material layer may be a mixture layer composed of a mixture of a positive electrode active material and other additive materials. Examples of the other additive materials include solid electrolytes such as inorganic solid electrolytes or sulfide solid electrolytes, conductive assistants such as acetylene black, and binding binders such as polyethylene oxide or polyvinylidene fluoride. The positive electrode active material layer can improve the lithium ion conductivity in the positive electrode active material layer and the electronic conductivity by mixing the positive electrode active material and other additive materials such as solid electrolytes at a predetermined ratio.

[0054] The thickness of the first active material layer 12 is, for example, not less than 5 μm and not more than 300 μm, but is not limited to this.

[0055] The second active material layer 22 is disposed in contact with one surface of the second current collector 21. In this embodiment, the second active material layer 22 is a negative electrode active material layer, and therefore the second active material layer 22 includes at least a negative electrode active material. The second active material layer 22 is a layer mainly composed of a negative electrode material such as a negative electrode active material. The negative electrode active material is a material in which metal ions such as lithium (Li) ions or magnesium (Mg) ions are inserted or extracted into or from the crystal structure at a potential lower than that of the positive electrode, and oxidation or reduction occurs accordingly. The type of positive electrode / negative electrode active material can be appropriately selected depending on the type of battery, and a known negative electrode active material can be used.

[0056] Examples of the negative electrode active material include carbon materials such as natural graphite, artificial graphite, graphite carbon fiber, and resin-sintered carbon, and alloy-based materials that are mixed with a solid electrolyte. Examples of the alloy-based materials include LiAl, LiZn, Li3Bi, Li3Cd, Li3Sb, Li4Si, Li 4.4 Pb, Li 4.4 Sn, Li 0.17 C or lithium alloys such as LiC6, lithium titanate (Li4Ti5O 12 ), zinc oxide (ZnO), or silicon oxide (SiO x) and other metal oxides can be used. For the negative electrode active material, only one of these materials may be used, or two or more of these materials may be used in combination.

[0057] As described above, the second active material layer 22 that becomes the negative electrode active material layer may contain at least a negative electrode active material. The negative electrode active material layer may be a mixture layer composed of a mixture of a negative electrode active material and other additive materials. Examples of the other additive materials include solid electrolytes such as inorganic solid electrolytes or sulfide solid electrolytes, conductive assistants such as acetylene black, and binding binders such as polyethylene oxide or polyvinylidene fluoride. The negative electrode active material layer can improve the lithium ion conductivity in the negative electrode active material layer and the electronic conductivity by mixing the negative electrode active material and other additive materials such as solid electrolytes at a predetermined ratio.

[0058] The thickness of the second active material layer 22 is, for example, not less than 5 μm and not more than 300 μm, but is not limited to this.

[0059] The solid electrolyte layer 30 is disposed between and in contact with the first active material layer 12 and the second active material layer 22. The solid electrolyte layer 30 includes at least a solid electrolyte. The solid electrolyte layer 30 includes, for example, a solid electrolyte as a main component.

[0060] The solid electrolyte may be any known solid electrolyte for batteries having ion conductivity. For example, a solid electrolyte that conducts metal ions such as Li lithium ions or Mg magnesium ions may be used as the solid electrolyte. The type of solid electrolyte may be appropriately selected according to the type of conductive ions. For example, an inorganic solid electrolyte such as a sulfide-based solid electrolyte or an oxide-based solid electrolyte may be used as the solid electrolyte. For example, a lithium-containing sulfide such as Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li2S-SiS2-LiI, Li2S-SiS2-Li3PO4, Li2S-Ge2S2, Li2S-GeS2-P2S5, or Li2S-GeS2-ZnS may be used as the sulfide-based solid electrolyte. For example, a lithium-containing metal oxide such as Li2O-SiO2 or Li2O-SiO2-P2O5, Li x P y O 1-z N z Lithium-containing metal nitrides such as Li3PO4, lithium phosphate (Li3PO4), and lithium-containing transition metal oxides such as lithium titanium oxide can be used. As the solid electrolyte, only one of these materials may be used, or two or more of these materials may be used in combination. In the present embodiment, the solid electrolyte layer 30 includes, as an example, a solid electrolyte having lithium ion conductivity.

[0061] In addition to the solid electrolyte material, the solid electrolyte layer 30 may contain an adhesive binder such as polyethylene oxide or polyvinylidene fluoride.

[0062] The thickness of the solid electrolyte layer 30 is, for example, not less than 5 μm and not more than 150 μm, but is not limited to this.

[0063] The solid electrolyte material may be configured as an aggregate of particles, or may have a sintered structure.

[0064] [Buffer layer] Next, a specific configuration of the buffer layer 40 will be described.

[0065] The buffer layer 40 is a layer having electrical conductivity. The buffer layer 40 is used for electrical connection between the solid-state battery cell 2 and another solid-state battery cell or another member. The buffer layer 40 also serves to cushion the solid-state battery cell 2 from shocks.

[0066] In this embodiment, the buffer layer 40 contains a PTC material 41 having electronic conductivity of PTC characteristics (positive temperature coefficient of resistance), a first metal 42, and a resin 43. The PTC material 41 is, for example, a BaTiO3-based semiconductor material. The first metal 42 is a metal with a low work function. For example, the first metal 42 is at least one selected from the group consisting of Sn (tin), Cu (copper), Al (aluminum), Mg (magnesium), and Zn (zinc), or an alloy thereof. The resin 43 is, for example, a thermosetting resin such as epoxy. Note that the resin 43 may be an insulating resin or a conductive resin. The conductive resin contains, for example, a thermosetting resin such as epoxy and conductive particles such as Ag. Alternatively, the conductive resin may be an insulating resin containing a conductive filler such as metal particles, or may be a conductive polymer that does not contain a conductive filler.

[0067] The first metal 42 and the PTC material 41 are crushed into particles and contained in the resin 43. The content ratio of each may be such that the PTC material 41 and the first metal 42 are contained so that the resistance-temperature characteristic of the buffer layer 40 exhibits the PTC characteristic, and further, the first metal 42 may be contained so that the temperature characteristic of the resistance value of the buffer layer 40 exhibits the PTC characteristic, and further, the buffer layer 40 exhibits a room temperature resistance level value corresponding to the content of the PTC material 41. By adopting such a configuration, a connection in a state of ohmic contact between the buffer layer 40 and the current collector, and between the interface between the PTC material 41 and the first metal 42 can be obtained. That is, there is no non-ohmic contact between the buffer layer 40 and the current collector, and between the PTC material 41 and the first metal 42. Therefore, the PTC characteristic can be added to the battery with low loss. If there is a non-ohmic contact, an interface resistance is added, and resistance loss is added to the battery characteristics.

[0068] For example, the resin 43 may contain 30 vol% to 80 vol% of the PTC material 41 and 5 vol% to 40 vol% of the first metal 42. Here, vol% is a ratio to the entire volume of the buffer layer 40. The content ratio can be appropriately adjusted depending on the dispersibility and resistance characteristics when contained in the resin 43. The electrical resistance of the buffer layer 40 can be measured by a four-terminal method or a four-probe method using a measuring device such as the Loresta series manufactured by Mitsubishi Analytic. For example, the thickness of the buffer layer 40 is 5 μm or more and 300 μm or less, but is not limited to this.

[0069] The electrical properties of the buffer layer 40 are expected to include electronic conductivity with PTC properties and ohmic contact with the current collector. The ohmic contact between the current collector and the buffer layer 40 can be evaluated from the presence or absence of polarity by evaluating the voltage-current characteristics in both directions under direct current. The ohmic contact between the powders of the PTC material 41 and the first metal 42 can also be directly confirmed from the presence or absence of polarity in microstructure evaluation using a nanoprober or the like. It goes without saying that a resistance value without polarity in the measurement direction indicates ohmic contact.

[0070] The PTC material 41 is, for example, particles obtained by crushing BaTiO3 semiconductor ceramics. Specifically, an N-type semiconductor in which a donor is formed in BaTiO3 is used as the PTC material 41. The donor is formed by substituting a small portion of the Ba site with a trivalent rare earth element such as yttrium (Y), or by substituting a portion of the Ti site with a pentavalent element such as niobium (Nb). The particle size of BaTiO3 is, for example, in the range of 0.2 μm to 10 μm.

[0071] The PTC material 41 may contain a small amount of transition elements such as manganese (Mn) or cobalt (Co) to improve the PTC characteristics. This can increase the jump in resistance value, especially when heat is generated, and clarify the switching performance of the PTC material 41. For example, the resistance value increases by about five to eight orders of magnitude when the PTC characteristics are expressed. This can reliably cut off the current and stop the operation of the battery.

[0072] The switching temperature may be increased from 120°C when no Ba site is used by replacing the Ba site with lead (Pb) having a larger ionic radius than the Ba ion. Alternatively, the switching temperature may be decreased by replacing the Ba site with strontium (Sr) having a smaller ionic radius than the Ba ion. The switching temperature is the temperature at which the resistance value of the PTC material 41 increases. For example, the switching temperature can be adjusted in the range of about 70°C to 250°C, and the temperature at which heat generation is suppressed can be arbitrarily controlled to a desired temperature. The switching temperature can also be reduced by replacing the Ti site with Sn. Furthermore, the withstand voltage and withstand current characteristics can be improved by, for example, reducing the size of the crystal grains. Furthermore, the reduction resistance can be improved by making Ba excessive in the ratio of Ba to Ti, or by using a trivalent semiconductor element. The Ba excess is, for example, in the range of +0.05% to +5.0% with respect to Ti. This can further increase the reliability of the battery operation and the reliability of the PTC characteristics against the outside air.

[0073] The first metal 42 may be any metal that makes ohmic contact with the PTC material 41. As a result, the first metal 42 also makes ohmic contact with the current collector. The first metal 42 is, for example, at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn. Alternatively, the first metal 42 may be at least one selected from the group consisting of Sn, Al, Mg, and Zn, excluding Cu, which is a metal element contained in a general conductive resin. In the case of the BaTiO3-based PTC material 41, if a metal having a work function smaller than that of Ag, which has a work function of about 4.5 eV to 4.7 eV, is used as the first metal 42, ohmic contact is easily formed. The first metal 42 may be in powder form. The particle size and shape of the first metal 42 are not particularly limited, but may be any metal that makes ohmic contact with the PTC material 41 and the current collector within a range that does not short-circuit the buffer layer 40. The first metal 42 may also contain a blend of metal particles having a work function lower than Ag and highly conductive particles such as Ag, Ni, Pd, or Pt. The type of first metal 42 may be appropriately adjusted within a range in which PTC characteristics can be obtained, taking into consideration the manufacturing process, such as ease of dispersion. The particle size of the first metal 42 is, for example, in the range of 0.1 μm to 10 μm. The particle shape of the first metal 42 is spherical or flat.

[0074] Furthermore, the buffer layer 40, containing the resin 43, is softer than the battery constituent members such as the current collector, and is more likely to form a connection state with a low Young's modulus. This absorbs the stress generated at the interface between the buffer layer 40 and the current collector, improving the durability of the connection interface against mechanical and thermal shocks and charge / discharge cycles. Furthermore, by having the PTC material 41 exist in the resin 43, the PTC material 41, which has poor environmental resistance, can be protected.

[0075] In addition, the resin 43 used in the buffer layer 40 may be a resin material with high gas and moisture sealing properties from the viewpoint of ensuring environmental resistance such as reduction of the BaTiO3-based PTC material 41. For example, the resin 43 does not have any communicating pores. In addition, the resin 43 may be a thermoplastic resin or a thermosetting resin. Examples of the thermoplastic resin include polyethylene resin, polypropylene resin, acrylic resin, polystyrene resin, vinyl chloride resin, silicone resin, polyamide resin, polyimide resin, fluorinated hydrocarbon resin, polyether resin, butadiene rubber, isoprene rubber, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-ethylene-butadiene-styrene copolymer (SEBS), ethylene-propylene rubber, butyl rubber, chloroprene rubber, and acrylonitrile-butadiene rubber. Examples of thermosetting resins include (i) amino resins such as urea resins, melamine resins, and guanamine resins; (ii) epoxy resins such as bisphenol A type, bisphenol F type, phenol novolac type, and alicyclic type; (iii) oxetane resins; (iv) phenol resins such as resol type and novolac type; and (v) silicone-modified organic resins such as silicone epoxy and silicone polyester.

[0076] Also, for example, the Young's modulus of the resin 43 of the buffer layer 40 is expected to be lower than that of the current collector, in terms of its function as the buffer layer 40. Also, the Young's modulus of the resin 43 is lower than that of the PTC material 41 and the first metal 42, for example. This alleviates the stress at the interface between the solid-state battery cell 2 and the buffer layer 40 caused by temperature change or external stress, and also absorbs the stress around the PTC material 41 and the first metal 42 in the buffer layer 40. This suppresses the occurrence of voids that connect to the outside and the occurrence of poor connection resistance. Furthermore, the buffer layer 40 deforms between the surface of the current collector and the PTC material 41 and the first metal 42 during the lamination and compression process, so that the bondability is improved. These effects allow the PTC characteristics to be obtained with high reliability.

[0077] Furthermore, from the viewpoint of alleviating stress between the solid battery cell 2 and the buffer layer 40 caused by expansion or contraction of the first active material layer 12 and the second active material layer 22 due to temperature change or charge / discharge, and improving the reliability of the PTC-equipped battery 1, the buffer layer 40 may be made of a material having a smaller Young's modulus than the solid electrolyte layer 30, the first active material layer 12, and the second active material layer 22. The relative relationship between these Young's moduli can be compared from the displacement characteristics or the size of the dent relative to the pressure when the probe is pressed into it.

[0078] The buffer layer 40 may be used by adjusting the type, shape and composition of each material in consideration of the ease of production in the manufacturing process, stress relaxation performance, thermal shock resistance and cold-heat cycle resistance. Pores may be formed in the buffer layer 40 so as not to penetrate the buffer layer 40, and the Young's modulus of the buffer layer 40 may be adjusted. It is desirable that the buffer layer 40 does not contain interconnected pores that cross the top and bottom in order to prevent the PTC material 41 from being exposed to a reducing atmosphere. The pore state can be confirmed by a normal cross-sectional observation method such as an optical microscope or an electron microscope. In addition, any cross section can also be analyzed by means such as a CT (Computed Tomography) scan. In addition, for a strict evaluation of the air permeability, the tissue can be taken out and confirmed by a method generally used in ceramic packages such as a nitrogen or helium leak tester. Such a tissue structure can also enhance the environmental resistance of the PTC characteristics in the buffer layer 40.

[0079] Furthermore, in the buffer layer 40, the resin 43 may contain a material in which particles of a conductive material or particles of a semiconductor material are contained in a solid electrolyte. This makes the expansion and contraction characteristics of the buffer layer 40 and the solid-state battery cell 2 closer to each other. This reduces the stress that occurs between the buffer layer 40 and the current collector during temperature changes or charging and discharging, making it possible to realize a battery 1 with highly reliable PTC characteristics.

[0080] The buffer layer 40 does not have to be formed on the entire surface of the current collector, and may be formed partially on the surface of the current collector in contact therewith, for example by patterning. In other words, the buffer layer 40 may be configured to be connected in series with the current collector. The buffer layer 40 may be configured with multiple layers of different materials, for example, multiple layers having different composition ratios of the PTC material 41 and the first metal 42.

[0081] In addition, the thickness of the buffer layer 40 is not particularly limited, but a thinner thickness is more advantageous in terms of the volumetric energy density of the battery 1. For this reason, the thickness of the buffer layer 40 may be thin as long as the reliability of the voltage resistance characteristics of the PTC can be ensured. The thickness of the buffer layer 40 is, for example, 1 μm or more and 100 μm or less, and preferably 2 μm or more and 10 μm or less. With this configuration, it is easy to alleviate stress caused by expansion or contraction of the current collector due to temperature change while suppressing a decrease in volumetric energy density.

[0082] In addition, the specific gravity of the buffer layer 40 is not particularly limited, but is preferably small from the viewpoint of weight energy density. For example, the specific gravity of the buffer layer 40 may be smaller than the specific gravity of the current collector made of a metal material. This can reduce the effect on weight energy density.

[0083] [Effects, etc.] When the configuration of battery 1 according to the present embodiment is compared with the configurations of the batteries described in Patent Documents 1 and 2, there are the following differences.

[0084] First, Patent Document 1 discloses an all-solid-state battery using a resin with PTC properties as a current collector. However, in the battery according to Patent Document 1, the PTC layer is formed using a carbon conductive agent such as acetylene black and a thermally expandable resin, which is different from the material constituting the buffer layer 40 according to the present embodiment. Therefore, the electrical resistance of the PTC material described in Patent Document 1 becomes high, which deteriorates the charge and discharge characteristics of the battery. In addition, the battery according to Patent Document 1 also has a problem with repeated use after expansion.

[0085] In contrast, in the battery 1 according to the present embodiment, the buffer layer 40 contains the first metal 42, and therefore makes ohmic contact with the current collector and the PTC material 41. This makes it possible to achieve low resistance in the buffer layer 40. Also, in the battery 1, the resin 43 of the buffer layer 40 is not a thermally expandable resin, and therefore expansion due to heat generation does not occur in the first place.

[0086] Furthermore, in Patent Document 1, a PTC layer is disposed on the active material surface. In other words, since the active material layer and the PTC layer are in contact with each other, the PTC layer is directly affected by the oxidation-reduction reaction on its surface. For this reason, there is a big problem with the stability of the battery operation.

[0087] Patent Document 2 also discloses an all-solid-state battery in which a PTC layer is disposed between an active material layer and a current collector. The PTC layer is made of a thermally expandable resin material as in Patent Document 1 and is disposed between the active material layer and the current collector. For this reason, the battery described in Patent Document 2, like Patent Document 1, increases the resistance loss of the battery, and has a problem with the stability of the battery operation.

[0088] In contrast, in the battery 1 according to the present embodiment, the buffer layer 40 containing the PTC material 41 is provided on the opposite side of the current collector to the side on which the active material layer is provided. This avoids contact between the PTC material and the active material layer, and suppresses the reduction of the PTC material. Note that Patent Documents 1 and 2 do not disclose or suggest a battery in which the buffer layer 40 described in the present embodiment, in which the PTC material 41 and the first metal 42 are contained in the resin 43, is provided on the opposite side of the current collector to the active material layer.

[0089] As described above, the battery 1 according to the present embodiment can suppress battery ignition and combustion with smoke caused by heat generation or overcurrent, thus realizing a highly reliable and high-performance battery 1.

[0090] [Variation 1] The following describes Modification 1 of the embodiment. In the following description of Modification 1, differences from the embodiment will be mainly described, and descriptions of commonalities will be omitted or simplified.

[0091] Fig. 2 is a diagram showing a schematic configuration of a battery according to Modification 1 of the embodiment. Specifically, Fig. 2(a) is a cross-sectional view of a battery 100 according to Modification 1, and Fig. 2(b) is a plan view of the battery 100 as viewed from the positive side in the z-axis direction. Fig. 2(a) shows a cross section taken along line II-II in Fig. 2(b). Fig. 2(c) is a cross-sectional view that is a schematic enlarged view of a portion of the cross-sectional shape shown in Fig. 2(a).

[0092] As shown in FIG. 2, the battery 100 according to the first modified embodiment is different from the battery 1 according to the embodiment in that it includes a buffer layer 140 instead of the buffer layer 40. The buffer layer 140 includes an alloy layer 144 in contact with the current collector. The alloy layer 144 mainly contains a second metal 142. The alloy layer 144 is a layer in which the low-melting-point second metal 142 is diffused into the current collector, and firmly bonds the current collector and the buffer layer 140. For example, the alloy layer 144 can be formed by diffusing the second metal 142 from the resin 43 to the current collector by hardening a PTC layer in which the second metal 142, which is a low-melting-point metal, is contained in a thermosetting resin.

[0093] Low melting point metal particles can be used as the second metal 142. For example, the second metal 142 is at least one selected from the group consisting of Sn (tin), Ag (silver), Cu (copper), bismuth (Bi), Al (aluminum) and Zn (zinc), or an alloy thereof. Alternatively, the second metal 142 may be at least one selected from the group consisting of Sn, Al, Mg and Zn, excluding Ag and Cu, which are metal elements contained in general conductive resins.

[0094] The low melting point metal is, for example, a metal having a melting point of 300° C. or less. Specifically, tin, tin-zinc alloy, tin-silver alloy, tin-copper alloy, tin-aluminum alloy, tin-lead alloy, indium, indium-silver alloy, indium-zinc alloy, indium-tin alloy, bismuth, bismuth-silver alloy, bismuth-nickel alloy, bismuth-tin alloy, bismuth-zinc alloy, or bismuth-lead alloy can be used. For example, when the current collector is Cu, if Sn is used as the second metal 142 and heat treatment is performed, an alloy layer 144 can be formed at the interface due to diffusion of the tin-copper alloy. In the case of a low melting point metal, it can be bonded even at a temperature of about half the melting point to obtain a strong bonding interface.

[0095] The content ratio of the second metal 142 is, for example, 1 vol % to 10 vol % in terms of volume ratio to the buffer layer 140. The components and amounts thereof are adjusted from the viewpoint of the thickness and bonding strength of the alloy layer 144. The thickness of the alloy layer 144 can also be appropriately adjusted by the heat treatment temperature.

[0096] Since the first metal 42 is a metal that can make ohmic contact with the PTC material 41, an appropriate metal is selected depending on the type of the PTC material 41. Since the second metal 142 is a metal that can form an alloy with the metal contained in the current collector, an appropriate metal is selected depending on the type of the current collector. As a result, the first metal 42 and the second metal 142 may be the same type of metal. Alternatively, the first metal 42 and the second metal 142 may be different types of metal.

[0097] As described above, the battery 100 according to the first modification can firmly bond the current collector and the buffer layer 140. This makes it possible to realize the battery 100 having more reliable PTC characteristics with respect to impact resistance, thermal cycles, and charge / discharge cycles.

[0098] [Variation 2] The following describes Modification 2 of the embodiment. In the following description of Modification 2, differences from the embodiment will be mainly described, and descriptions of commonalities will be omitted or simplified.

[0099] Fig. 3 is a diagram showing a schematic configuration of a battery according to Modification 2 of the embodiment. Specifically, Fig. 3(a) is a cross-sectional view of a battery 200 according to Modification 2, and Fig. 3(b) is a plan view of the battery 200 as viewed from the positive side in the z-axis direction. Fig. 3(a) shows a cross section taken along line III-III in Fig. 3(b). Fig. 3(c) is a cross-sectional view in which a part of the cross-sectional shape shown in Fig. 3(a) is enlarged in schematic form.

[0100] 3, battery 200 according to the second modification of the embodiment differs from battery 1 according to the embodiment in that it includes a buffer layer 240 instead of buffer layer 40. Buffer layer 240 has a three-layer structure including a PTC layer 241 and two conductive resin layers 242 and 243 disposed to sandwich PTC layer 241 from both sides.

[0101] The PTC layer 241 includes the above-mentioned PTC material. For example, the PTC layer 241 is a layer made of the PTC material 41 formed into a plate shape. Alternatively, the PTC layer 241 may be a layer made of particulate PTC material 41 formed into a layer shape using a binding binder or the like.

[0102] The conductive resin layers 242 and 243 each contain a first metal 42 and a resin 43. The conductive resin layer 242 covers the surface of the PTC layer 241 opposite to the current collector.

[0103] The conductive resin layer 243 covers the surface of the PTC layer 241 facing the current collector. The conductive resin layer 243 is disposed between the current collector and the PTC layer 241 and is in contact with each other. That is, the PTC layer 241 is electrically connected to the current collector via the conductive resin layer 243 containing the first metal 42. This ensures ohmic contact with the PTC layer 241 and can suppress the increase in resistance of the buffer layer 240. Such a three-layer structure realizes ohmic contact on both sides of the PTC layer 241 while protecting the PTC layer 241.

[0104] The thicknesses of the three layers can be adjusted appropriately from the viewpoints of the manufacturing method and characteristics. The alloy layer 144 shown in the first modification may be formed between the conductive resin layer 243 and the current collector. The conductive resin layers 242 and 243 may contain the first metal 42 so as to be in ohmic contact with the PTC layer 241, and may contain Ag particles or other conductive metals having electronic conductivity. In order to effectively obtain the PTC characteristics, the present modification is not limited as long as the PTC characteristics can be derived from the PTC layer 241 mainly via the first metal 42.

[0105] As described above, the battery 200 according to the second modification can suppress battery ignition and combustion with smoke caused by heat generation or overcurrent, thus realizing a highly reliable and high-performance battery 200.

[0106] [Variation 3] The following describes Modification 3 of the embodiment. In the following description of Modification 3, differences from the embodiment or Modification 2 will be mainly described, and descriptions of commonalities will be omitted or simplified.

[0107] Fig. 4 is a diagram showing a schematic configuration of a battery according to Modification 3 of the embodiment. Specifically, Fig. 4(a) is a cross-sectional view of a battery 300 according to Modification 2, and Fig. 4(b) is a plan view of the battery 300 as viewed from the positive side in the z-axis direction. Fig. 4(a) shows a cross section taken along line IV-IV in Fig. 4(b). Fig. 4(c) is a cross-sectional view showing a schematic enlargement of a portion of the cross-sectional shape shown in Fig. 4(a).

[0108] 4, compared to battery 200 according to modification 2, battery 300 according to modification 3 of the embodiment includes a buffer layer 340 instead of buffer layer 240. Buffer layer 340 includes a metal layer 343 instead of conductive resin layer 243.

[0109] The metal layer 343 includes the first metal described above. For example, the metal layer 343 is a layer made of the first metal 42 formed into a plate shape. The metal layer 343 does not include the resin 43.

[0110] Even in this configuration, the PTC layer 241 is electrically connected to the current collector via the metal layer 343. This ensures ohmic contact with the PTC layer 241 and prevents the buffer layer 340 from becoming highly resistive.

[0111] The thickness of the metal layer 343 can be adjusted appropriately in view of the manufacturing method and characteristics. Furthermore, the alloy layer 144 shown in the first modification may be formed between the metal layer 343 and the current collector.

[0112] As described above, the battery 300 according to the third modification can suppress battery ignition and combustion with smoke caused by heat generation or overcurrent, thus realizing a highly reliable and high-performance battery 300.

[0113] [Variation 4] The following describes Modification 4 of the embodiment. In the following description of Modification 4, differences from the embodiment will be mainly described, and descriptions of commonalities will be omitted or simplified.

[0114] FIG. 5 is a diagram showing a schematic configuration of a particulate PTC material and a first metal in a buffer layer in a battery according to Modification 4. As shown in FIG. 5, the surface of the particulate PTC material 41 is coated with a first metal layer 442. In the embodiment, the particulate PTC material 41 and the particulate first metal 42 are mixed and dispersed, but in Modification 4, the particulate PTC material 41 is coated with a first metal layer 442. The origin of the PTC characteristic of the BaTiO3 semiconductor is the crystal grain interface. For this reason, the particulate PTC material 41 is preferably a polycrystalline particle having directly bonded grain boundaries.

[0115] With this configuration, the particulate PTC material 41 and the first metal layer 442 are connected by a surface connection. Therefore, the conductive area of ​​the connection interface is significantly increased compared to point contact between powder particles. This makes it possible to bring out the characteristics of the PTC material 41 while further reducing resistance loss, and also to improve the protective performance of the PTC material 41. This makes it possible to realize a battery with high-performance PTC characteristics and higher reliability.

[0116] The coating of first metal layer 442 can be formed by powder coating such as a mechanical particle composite process, or by electroless plating of particulate PTC material 41. The coating thickness of first metal layer 442 is, for example, 1 μm or less.

[0117] As described above, the battery according to Modification 4 can suppress battery fire and combustion with smoke caused by heat generation or overcurrent, thus realizing a highly reliable and high-performance battery.

[0118] The PTC material 41 coated with the first metal layer 442 according to the modification 4 can be contained in the resin 43 as the PTC material 41 in the embodiment and each of the modifications 1 to 3. In this case, the resin 43 does not need to contain the particulate first metal 42.

[0119] [Variation 5] The following describes Modification 5 of the embodiment. In the following description of Modification 5, differences from the embodiment will be mainly described, and descriptions of commonalities will be omitted or simplified.

[0120] Fig. 6 is a diagram showing a schematic configuration of a battery according to Modification 5 of the embodiment. Specifically, Fig. 6(a) is a cross-sectional view of a stacked battery 500 according to Modification 5, and Fig. 6(b) is a plan view of the stacked battery 500 as viewed from the positive side in the z-axis direction. Fig. 6(a) shows a cross section taken along line VI-VI in Fig. 6(b).

[0121] As shown in FIG. 6, a stacked battery 500 according to Modification 5 differs from the battery 1 according to the embodiment in that two solid-state battery cells 2 are stacked and connected via a buffer layer 40.

[0122] The two solid-state battery cells 2 are an example of a first solid-state battery cell and a second solid-state battery cell, respectively. The two solid-state battery cells 2 are stacked with a buffer layer 40 interposed therebetween and are electrically connected in series to each other.

[0123] 6, the positive electrode current collectors of two solid-state battery cells 2 are connected to each other. As described in the embodiment, the first current collector 11 may be a negative electrode current collector. In other words, the stacked battery 500 may include two solid-state battery cells 2 whose negative electrode current collectors are connected to each other. The number of stacked solid-state battery cells 2 may be three or more.

[0124] With this configuration, if a short circuit or abnormal heat generation occurs in one of the solid-state battery cells 2, the current is cut off due to the PTC characteristic of the buffer layer 40. The buffer layer 40 can connect the solid-state battery cells 2 together ohmically with the PTC characteristic, so that a low-loss series-stacked battery with PTC characteristics can be configured.

[0125] As described above, the stacked battery 500 according to the fifth modification can prevent battery fire and combustion with smoke caused by heat generation or overcurrent, thus realizing a highly reliable, large-capacity battery.

[0126] [Battery manufacturing method] Next, an example of a method for manufacturing the battery according to this embodiment will be described. The method for manufacturing the battery 1 according to the above-mentioned embodiment will be described below. First, pastes used for printing the first active material layer (hereinafter, positive electrode active material layer) 12 and the second active material (hereinafter, negative electrode active material layer) 22 are prepared. As a solid electrolyte raw material used for the mixture of the positive electrode active material layer and the negative electrode active material layer, for example, a glass powder of Li2S-P2S5-based sulfide mainly composed of triclinic crystals and having an average particle size of about 10 μm is prepared. As this glass powder, for example, 2×10-3 S / cm to 3×10 -3 As the positive electrode active material, for example, a Li·Ni·Co·Al composite oxide (specifically, LiNi 0.8 Co 0.15 Al 0.05 O2) powder is used. A paste for a positive electrode active material layer is prepared by dispersing a mixture containing the above-mentioned positive electrode active material and the above-mentioned glass powder in an organic solvent or the like. As the negative electrode active material, for example, a powder of natural graphite having an average particle size of about 10 μm is used. A paste for a negative electrode active material layer is prepared in the same manner by dispersing a mixture containing the above-mentioned negative electrode active material and the above-mentioned glass powder in an organic solvent or the like.

[0127] Next, a copper foil having a thickness of, for example, about 30 μm is prepared as a material used for the first current collector 11 (hereinafter, positive electrode current collector) and the second current collector 21 (hereinafter, negative electrode current collector). The paste for the positive electrode active material layer and the paste for the negative electrode active material layer are printed on one surface of each copper foil by a screen printing method in a predetermined shape and with a thickness of about 50 μm to 100 μm. The paste for the positive electrode active material layer and the paste for the negative electrode active material layer are dried in a range of 80° C. to 130° C. to have a thickness of about 30 μm to 60 μm. This provides the current collectors (copper foils) on which the positive electrode active material layer and the negative electrode active material layer are formed, that is, the first electrode 10 (hereinafter, positive electrode) and the second electrode 20 (hereinafter, negative electrode).

[0128] Next, a paste for a solid electrolyte layer is prepared by dispersing the mixture containing the above-mentioned glass powder in an organic solvent or the like. The above-mentioned paste for a solid electrolyte layer is printed, for example, to a thickness of about 100 μm on the surfaces of the active material layers of the positive and negative electrodes using a metal mask. Then, the positive and negative electrodes on which the paste for a solid electrolyte layer is printed are dried at a temperature in the range of 80° C. to 130° C.

[0129] Next, the solid electrolyte printed on the positive electrode active material layer of the positive electrode and the solid electrolyte printed on the negative electrode active material layer of the negative electrode are laminated so as to be in contact with and face each other.

[0130] Next, a 5×10 elastic modulus was applied to the top surface of the current collector between the pressing mold plate and the current collector. 6 An elastic sheet having a pressure of about 300 MPa is inserted. The thickness of the elastic sheet is, for example, 70 μm. Then, the pressurizing mold plate is pressed at a pressure of 300 MPa for 90 seconds while being heated to 50° C.

[0131] Through the above steps, the solid-state battery cell 2 is produced.

[0132] Next, a particulate PTC material 41 (specifically, BaTiO3-based semiconductor) having an average particle size of about 1 μm and a powder of a first metal 42 having an average particle size of 0.5 μm are added to a thermosetting conductive resin paste containing silver particles having an average particle size of 0.5 μm, and dispersed using a triple roll to prepare a resin paste containing the PTC material 41 and the first metal 42 (i.e., a resin paste for the buffer layer 40). Next, the resin paste for the buffer layer 40 is printed on the collector surface of the prepared solid-state battery cell 2 using a metal mask. Next, a heat curing process is performed in a dryer at 120° C. for one hour, and the resin paste for the buffer layer 40 is cooled to room temperature to form the buffer layer 40.

[0133] The battery 1 is manufactured through the above steps. Note that the method and order of forming the battery 1 are not limited to the above example.

[0134] In the above-mentioned manufacturing method, the positive electrode active material layer paste, the negative electrode active material layer paste, the solid electrolyte layer paste, and the resin paste for the buffer layer 40 are applied by printing, but the method is not limited to this. As the printing method, for example, a doctor blade method, a calendar method, a spin coating method, a dip coating method, an inkjet method, an offset method, a die coating method, a spray method, etc. may be used.

[0135] In the above-mentioned manufacturing method, the resin paste for the buffer layer 40 is a thermosetting conductive resin paste containing silver metal particles, but is not limited thereto. The conductive resin paste may be a thermosetting conductive resin paste containing highly conductive metal particles having a high melting point of, for example, 400° C. or more, or a low melting point metal particle and resin, for example, 300° C. or less, which is lower than the hardening temperature of the conductive resin paste. Examples of the material of the highly conductive metal particles having a high melting point include silver, copper, nickel, zinc, aluminum, palladium, gold, platinum, or an alloy of these metals. Examples of the material of the low melting point metal particles having a melting point of 300° C. or less include tin, tin-zinc alloy, tin-silver alloy, tin-copper alloy, tin-aluminum alloy, tin-lead alloy, indium, indium-silver alloy, indium-zinc alloy, indium-tin alloy, bismuth, bismuth-silver alloy, bismuth-nickel alloy, bismuth-tin alloy, bismuth-zinc alloy, or bismuth-lead alloy. By using such a conductive resin paste containing low melting point metal particles, solid and liquid phase reactions proceed at the contact points between the metal particles in the conductive resin paste and the metal constituting the current collector, even at a heat curing temperature lower than the melting point of the high melting point highly conductive metal particles. As a result, a diffusion region alloyed by solid and liquid phase reactions is formed around the contact points at the interface between the conductive resin paste and the surface of the current collector. This can be used as an alloy layer 144 that firmly bonds the interfaces.

[0136] Examples of the alloy formed include a highly conductive silver-copper alloy when silver or a silver alloy is used for the conductive metal particles and copper is used for the current collector. Furthermore, a silver-nickel alloy or a silver-palladium alloy may be formed by combining the conductive metal particles with the current collector. This configuration provides a stronger bond between the current collector and the buffer layer, and thus provides an effect of preventing the bonded portion from peeling off due to, for example, a thermal cycle or impact.

[0137] The shape of the high melting point highly conductive metal particles and the low melting point metal particles may be any shape, such as spherical, flaky, needle-like, etc. The particle size of the high melting point highly conductive metal particles and the low melting point metal particles is not particularly limited. For example, the smaller the particle size, the lower the alloy reaction and diffusion progress at, so the particle size and shape are appropriately selected in consideration of the effect of heat history on process design and battery characteristics.

[0138] The resin used in the thermosetting conductive resin paste may be any resin that functions as a binder for bonding, and may be selected appropriately depending on the manufacturing process to be adopted, such as printability and coatability. The resin used in the thermosetting conductive resin paste includes, for example, a thermosetting resin. Examples of the thermosetting resin include (i) amino resins such as urea resin, melamine resin, and guanamine resin, (ii) epoxy resins such as bisphenol A type, bisphenol F type, phenol novolac type, and alicyclic type, (iii) oxetane resin, (iv) phenol resins such as resol type and novolac type, and (v) silicone-modified organic resins such as silicone epoxy and silicone polyester. Only one of these materials may be used as the resin, or two or more of these materials may be used in combination.

[0139] (Other embodiments) Although the battery according to the present disclosure has been described above based on the embodiments, the present disclosure is not limited to these embodiments. As long as it does not deviate from the gist of the present disclosure, various modifications conceivable by a person skilled in the art to the embodiments and other forms constructed by combining some of the components in the embodiments are also included in the scope of the present disclosure.

[0140] Furthermore, the above-described embodiment can be modified, replaced, added, omitted, and the like in various ways within the scope of the claims or their equivalents. [Industrial Applicability]

[0141] The battery according to the present disclosure can be used, for example, as a secondary battery such as an all-solid-state battery for use in various electronic devices or automobiles. [Explanation of symbols]

[0142] 1, 100, 200, 300 batteries 2 Solid-state battery cells 10 First electrode (positive electrode) 11 First current collector (positive electrode current collector) 12 First active material layer (positive electrode active material layer) 20 Second electrode (negative electrode) 21 Second current collector (negative electrode current collector) 22 Second active material layer (negative electrode active material layer) 30 Solid electrolyte layer 40, 140, 240, 340 buffer layer 41 PTC material 42 Daiichi Metals 43 Resin 142 Second metal 144 Alloy layer 241 PTC layer 242, 243 Conductive resin layer 343 Metal layer 442 First metal layer 500 stacked battery

Claims

1. a first solid-state battery cell; A buffer layer; Equipped with the first solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode; The positive electrode or the negative electrode has a current collector, the buffer layer is in contact with a surface of the current collector opposite to the solid electrolyte layer, the buffer layer includes a PTC material, a resin, and a first metal; The first metal is at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn, The buffer layer includes a PTC layer and a conductive resin layer, the PTC layer includes the PTC material; the conductive resin layer contains the resin and the first metal, and does not contain the PTC material; The conductive resin layer covers a surface of the PTC layer opposite to the current collector. battery.

2. The first metal is at least one selected from the group consisting of Sn, Al, Mg, and Zn.

10. The battery of claim 1.

3. The conductive resin layer further covers a surface of the PTC layer facing the current collector.

10. The battery of claim 1.

4. the buffer layer includes a metal layer covering a surface of the PTC layer facing the current collector, The metal layer includes the first metal.

10. The battery of claim 1.

5. A first solid-state battery cell; A buffer layer; Equipped with the first solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode; The positive electrode or the negative electrode has a current collector, the buffer layer is in contact with a surface of the current collector opposite to the solid electrolyte layer, the buffer layer includes a PTC material, a resin, and a first metal; The first metal is at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn, the buffer layer comprises an alloy layer in contact with the current collector, the alloy layer is made of an alloy including a second metal; The second metal is at least one selected from the group consisting of Sn, Ag, Cu, Bi, Al, and Zn; battery.

6. The second metal is at least one selected from the group consisting of Sn, Bi, Al, and Zn.

6. The battery of claim 5.

7. A first solid-state battery cell; A buffer layer; Equipped with the first solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode; The positive electrode or the negative electrode has a current collector, the buffer layer is in contact with a surface of the current collector opposite to the solid electrolyte layer, the buffer layer includes a PTC material, a resin, and a first metal; The first metal is at least one selected from the group consisting of Sn, Cu, Al, Mg, and Zn, the PTC material is in the form of particles; the particles are coated with the first metal; battery.

8. Further comprising a second solid-state battery cell; The first solid-state battery cell and the second solid-state battery cell are stacked with the buffer layer interposed therebetween. The battery of any one of claims 1 to 7.

9. The solid electrolyte layer contains a solid electrolyte having lithium ion conductivity.

9. The battery of claim 1 .

Citation Information

Patent Citations

  • Bipolar secondary battery

    JP2011048932A

  • All-solid battery manufacturing method

    JP2017130281A

  • All-solid battery

    JP2018116810A

  • Laminate battery

    JP2018181524A

  • Electrode current collector and all solid state battery

    JP2018200784A